Mycobacterium chimaera – a new threat for cardiac surgical patients? - Jaworski, Radosław; Naumiuk, Łukasz; Paczkowski, Konrad; Formella, Danuta; Pek, Renata; Zieliński, Jacek; Haponiuk, Ireneusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2017)
An outbreak of invasive Mycobacterium chimaera infections associated with “heater-cooler” devices in patients treated with cardiac surgery has been described worldwide. The authors summarize the current state of knowledge regarding the epidemiology, diagnostics, treatment, and prevention of Mycobacterium chimaera infections in patients after cardiothoracic surgery.